Social capital of communicative fields of the scientific community - Valnistaya, Marina G.; Mamеdov Agamali K. (Journal of the Belarusian State University. Sociology, 2019)
The article presents an expanded definition of social capital created in the field of scientific communications. The authors consider the process of formation of the social capital of science at the stages of the genesis of the scientific interaction of the community of scientists. The article analyzes the forms of existence of social capital and justifies the principles by which necessary conditions for the formation of social capital are created through scientific communications. The moral-ethical, axiological, epistemological aspects and channels of scientific interaction in the modern scientific community are considered, the boundaries of the scientist’s social responsibility for the results of his activity are determined.